PENGARUH PENGGUNAAN MEDIA FLIP CHART TERHADAP HASIL BELAJAR SISWA DI MTs AS-SALAFIYAH PAKONG PAMEKASAN - Mustafidatul; Abdullah (Journal of Education Partner, 2022)
One of the learning media that can improve student learning outcomes is Flip Chart media that can affect student learning outcomes, thus, then there are two formulations in this study, first is the influence of Flip Chart media use on student learning outcomes?, second how much influence does the use of Flip Chart media have on student learning outcomes? In this study, researchers used a quantitative approach, with statistical data analysis, this study is a correlation study using the Formula Product Moment. The subjects in this study were students at madrasah Tsanawiyah As-Salafiyah who were sampled with a total of 21 students, while the method of data collection was a method of questionnaire, interview, observation and documentation. The results showed that: 1). There is an Influence on the Use of Flip Chart Learning Media On The Learning Outcomes of MTs As-Salafiyah Students Source Duko Pakong Pamekasan. This is evidenced by the results of the product moment calculation, that the work "r" is greater than the "r" price of criticism which is 0.75>0.432 at a significant level of 5% and 0.549 at a significant level of 1%. 2). The Use of Flip Chart Learning Media Against Student Learning Outcomes of Class VIII Fiqh Subjects in MTs As-Salafiyah Sumber Duko Pakong Pamekasan has a high/ strong level of influence. Based on the results of research on the table of interpretation r product moment known "r" work of 0.75 turned out to be between the range of values 0.70-0.90 with high interpretation/ strong.